Long-Term Stability of Lavandula x intermedia Essential Oil Nanoemulsions: Can the Addition of the Ripening Inhibitor Impact the Biocidal Activity of the Nanoformulations? - Stefania Petralito; Stefania Garzoli; Elisa Ovidi; Valentina Laghezza Masci; Jordan Trilli; Barbara Bigi; Laura Di Muzio; Vito Cosimo Carriero; Maria Antonietta Casadei; Patrizia Paolicelli (MDPI AG, 2024)
In this work, Lavandula x intermedia essential oil (LEO) was encapsulated in lipid-based nanoemulsions (NanoLEO) using the solvent-displacement technique. In order to preserve the colloidal stability of the formulation, LEO was appropriately doped with the incorporation of different levels of a water-insoluble oil used as a ripening inhibitor. All the nanoemulsion samples were evaluated in terms of the impact of the water-insoluble oil on the nanoemulsion formation, physical-chemical properties, and antibacterial effectiveness against E. coli (Gram-negative) and B. cereus (Gram-positive). The presence of the inert oil added benefits to the formulations in terms of appearance, colloidal stability, and loss of volatile components. However, the antimicrobial activity of the nanoemulsions dramatically decreased with the ripening inhibitor addition, probably because it hampered the internalization of the antimicrobial components of LEO within the bacterial cell membranes, thus nullifying the delivery ability of the nanoemulsion formulation. On the contrary, the undoped NanoLEO formulation showed unaltered antibacterial activity in both E. coli and B. cereus up to 40 weeks from the preparation.